Analysis of Errors Committed by Students in Writing English Essays - Sharma, Lok Raj (International Research Journal of MMC, 2021)
Error analysis in linguistics is a systematic process of collecting, identifying, describing, explaining and evaluating unaccepted linguistic forms committed by learners in their writings or speeches. This article attempts to assess the errors committed by 128 bachelor first year education students studying English as a foreign language at Makawanpur Multiple Campus, Hetauda, Nepal in the year 2021. Every student was assigned to write an essay on ‘The Impact of Corona Pandemic on Students’ in about 500 words as the written language sample in a free mode. 128 essays were selected as a sample through the simple random sampling method lottery from 190 essays. All the errors in their essays were identified, described, classified, explained and analyzed. The results revealed that most of the students committed errors in omission at the sentence level, and the causes of the errors were due to intralingual transfer, whereas the highest frequency of errors at the word level was preposition resulted due to mother tongue transfer and overgeneralization.